Trust (Amanah) Competence - Poerbantoro, Heri; Sukamto, Sukamto; Andini, Rita; Handayani, Tri; Sulistyawati, Dwi Retna (Journal Research of Social Science, Economics, and Management, 2024)
This article aims to describe the relationship between the competence concept and the Islamic value of trust (amanah). Trust (amanah) competence is an ability of a person to incorporate a set of knowledge, skills, and trust based on the nature of integrity, sincerity, and responsibility, in order to obtain happiness and success. The new concept of competence requirement is expected to become the foundation for human resource development, so that competent professionals would avoid bad behavior and corruption. This study’s contribution to the Resource-Based View Theory, particularly its emphasis on competence, is founded on knowledge and trustworthiness.